Narrativas infantis e figurações da convivência: uma proposta de discussão e seleção de textos - Bessa, Luiza Gomes dos Santos (2022)
This dissertation aims to present reflections on how children's literary narratives can be an impulse to imagine values that corroborate a more welcoming social coexistence. In the wake of this reflection, it will be possible to perceive that literary texts have the potential to sensitize, problematize, question and trigger discussions, allowing children to see extrafictional behaviors and to transfer the knowledge obtained through narratives to everyday situations. The dissertation is divided into six parts, the first and second sections aim to expose how the social and cultural context is fragmented, dynamic and plural, how children who emerge from this context are affected by this fragmentation in the construction of their own identity and how the education process is vital in rising awareness to live with diversity and differences in contemporary times. The third section will discuss the topic of living with ethnic-cultural diversity, in which four works of children's literature will be analyzed, focusing on black and indigenous characters. The literary analysis discusses the following works: Menina bonita do laço de fita by Ana Maria Machado (2011a), O cabelo de Lelê by Valéria Belém (2012), Abaré by Graça Lima (2009) and Menino Poti by Ana Maria Machado (2011b). The fourth part is focused on the dynamics of values on the axis of bodily differences, discussing Ninguém é igual a Ninguém by Regina Otero e Regina (1994), Deixa eu te contar menino, Deixa eu te contar menina by Thaís Vilarinho (2019), Uma formiga especial by Márcia Honora (2008) and Um amigo diferente? by Claudia Werneck (1996). The fifth part focuses on the values of living with family diversity, since family represents a privileged space to glimpse essential values for living together. This section focuses on As famílias do mundinho by Ingrid Biesemeyer Bellinghausen (2006), Cada um com seu jeito, cada jeito é de um by Lucimar Rosa Dias (2012), A Família do Marcelo by Ruth Rocha (2001) e Cada família é de um jeito by Aline Abreu (2006). Finally, the last chapter will discuss the relevance of values in the cultivation of feelings. To discuss this theme, following texts will be discussed: A ovelha rosa da dona Rosa by Donaldo Buchweitz (2019), O Amigo do Rei by Ruth ROCHA (2009), Inclusão No Coração: A fábula do grilinho e do vaga-lume by Pedro Paulo da Luz (2011) and A Menina e o pássaro encantado by Rubem Alves, (2020). The choice of these sixteen literary texts was based on the experience in the school environment, characterized by ethnic-cultural, social, corporal and family diversity, and aimed to seek texts written for children that could contemplate this diversity. The path followed was based on the belief that the fictional universe, in addition to its aesthetic character, can offer impulses to the child to imagine values such as respect, kindness, empathy, dialogue and acceptance, recognizing equal rights and cooperating to live with differences. Key theorists that will be revisited to support the discussions are Fanny Abramovich (1997), Nelly Novaes Coelho (2000), Gregorin Filho (2009a, 2009b), Silveira et al. (2012), Regina Zilberman (2003) and others.